Endoscopic third ventriculostomy is a safe and effective procedure for the treatment of Blake's pouch cyst - Carlos Vicente Brusius; Sergio Cavalheiro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Blake's pouch cyst (BPC) is a midline cystic malformation of the posterior fossa, within Dandy-Walker's complex (DWC), often associated with hydrocephalus. Endoscopic third ventriculostomy (ETV) has been an alternative to conventional methods for BPC treatment. This study aimed at reporting our experience with ETV in a series of patients with BPC. METHODS: Of 33 patients diagnosed with midline posterior fossa cyst, 26 met the protocol criteria for DWC, and eight subjects with BPC were selected (aged one month to two years old). All cases were treated with ETV. RESULTS: Five patients were male; and three were prenatally diagnosed. They had hydrocephalus and motor deficiencies. Motor assessment at a five-year follow-up yielded normal findings. All patients improved, and only one had residual cognitive dysfunction, despite overall neurological improvement. There were no complications. CONCLUSIONS: ETV was a safe and effective procedure, reducing risks and morbidity associated with open surgery and shunt-related problems.